Seasonal variation of microbial community and methane metabolism in coalbed water in the Erlian Basin, China - Fu, Li; Lai, Shouchao; Zhou, Zhuo; Chen, Zhenhong; Cheng, Lei (Frontiers in Microbiology, 2023)
Coalbed water is a semi-open system connecting underground coalbeds with the external environment. Microorganisms in coalbed water play an important role in coal biogasification and the carbon cycle. The community assemblages of microorganisms in such a dynamic system are not well understood. Here, we used high-throughput sequencing and metagenomic analysis to investigate microbial community structure and identify the potential functional microorganisms involved in methane metabolism in coalbed water in the Erlian Basin, a preferred low-rank coal bed methane (CBM) exploration and research area in China. The results showed that there were differences in the responses of bacteria and archaea to seasonal variation. Bacterial community structure was affected by seasonal variation but archaea was not. Methane oxidation metabolism dominated by Methylomonas and methanogenesis metabolism dominated by Methanobacterium may exist simultaneously in coalbed water.